Dengue Haemorrhagic Fever and House Conditions in Kupang City, East Nusa Tenggara Province - Wanti, Wanti; Yudhastuti, Ririh; Notobroto, Hari Basuki; Subekti, Sri; Sila, Oktofianus; Kristina, Ragu Harming; Dwirahmadi, Feby (UI Scholars Hub, 2019)
Kupang City has the highest Incidence of DHF in East Nusa Tenggara and also higher than the national figure. This study aims to analyze the relationship between housing conditions and the DHF incidence in the Kupang City. This observational study uses a case-control study in 25 villages with a total sample of 500 people. Data is analyzed using t test and chi square test. The house conditions were significantly related to the DHF incidence (p≤0.05), namely house lighting, water usage, wall construction, ventilation area and ownership of clean water facilities. People are advised to ventilate the house ≥10% of the floor area and often open the house ventilation as a place for air exchange and for entering the light into the house. Construction of the wall is expected to be repaired to be more permanent or close the open part so not as a mosquitoes path into the house. The government is advised to increase access to clean water for the community and promote to always clean water reservoirs and not hold water for a long time.